The Technique and Application of Ultrasound in the Diagnosis and Management of Inflammatory Arthritis - Rowbotham, Emma L.; Wakefield, Richard J.; Grainger, Andrew J. (Seminars in Musculoskeletal Radiology, 2012)
Ultrasound is increasingly used by radiologists and rheumatologists for the diagnosis and assessment of inflammatory arthritis in day-to-day clinical practice. It is ideally suited to demonstrating early changes of these conditions before they are evident using conventional radiography or indeed clinical examination. Ultrasound readily demonstrates synovitis, effusion, soft tissue changes, and some bone features (including erosion and enthesophyte formation) of inflammatory arthritis. It also provides a way to quantify disease activity. This article reviews the ultrasound imaging features of the inflammatory arthritides and techniques involved. It also highlights the advantages and disadvantages of ultrasound as opposed to magnetic resonance imaging.
Keywords: ultrasound; synovitis; erosion; rheumatoid arthritis